An experimental and numerical investigation of absorber positioning in a natural convection solar drying system - Predolin, Rodrigo Eduardo [UNESP]; Ito, Mario Cesar [UNESP]; Palma, Geraldo Luiz [UNESP]; Scalon, Vicente Luiz [UNESP] (Elsevier, 2022)
The known advantages of drying food are long term preservation, weight reduction and, consequently, minimizing the transportation and storage costs. Drying technology can also spoil the conditions for microbial growth. In this study, an indirect solar dryer with natural convection was developed, constructed and experimentally investigated for using in remote regions. It comprises three main parts: an absorber plate with 0.5 m2 surface area, a dryer chamber and an exhaust duct. The absorber plate position can be modified in this device and change the airflow conditions from over the upper face only to the upper and lower face (double passage). Tests changing this position increased the product humidity removal rate from 0.47 g/min to 0.56 g/min, the total water removal over the day from 185 g to 220 g and the average daily thermal efficiency from 8.5% to 19.8%. The equipment performance evaluation was possible due to the presence of temperature, humidity and atmospheric pressure sensors positioned at the air inlet and outlet. A turbine-type anemometer at the air outlet was used for airflow measurements. The other three temperature sensors placed on the absorber plate and a load cell located in the drying chamber are also used. The evaporation process was recorded based on load cells installed in the drying chamber. Another model was also applied to calculate the same parameter using the mass balance. A CFD model was build to compare with the experimental results and good agreement was found. Comparison for different solar dryer setups show a better efficiency when the absorber plate is positioned in the middle of the inlet flow.
Keywords: Convective solar dryer; Indirect solar dryer; Solar absorber panel; Thermal efficiency